Synthesis of 1,1-dibutoxyethane in a simulated moving bed adsorptive reactor - Graça, Nuno S. (2014)
The synthesis of 1,1-Dibutoxyethane was carried out in a Simulated Moving Bed pilot unit LICOSEP 12-26 (Novasep, France) with 12 columns packed with the commercial ionexchange resin Amberlyst 15 (Rohm & Haas, France). Experimentally it was obtained a raffinate purity of 85% with a productivity of 5,04 Kg.L-1.d-1 and a desorbent consumption of 15, 5 L.Kg-1. The influence of the different operation parameters was studied by simulation. The results showed that the SMBR process presents a potential to be a competitive, efficient and environmentally friendly way to produce 1,1- Dibutoxyethane and other acetals.